Shifting baseline syndrome in the fishing community of Barcelona: insights from scientific and local ecological knowledge - Edoardo Zelli; Océane Legatelois; Laura Calvet-Mir; Irene Iniesta-Arandia; Sara Miñarro (Ecology and Society, 2025)
The escalating human-driven pressures, such as coastal development, climate change, and overfishing, have led to habitat degradation and declines in marine resource abundance. These impacts pose significant threats to the livelihoods of coastal communities, particularly in the Mediterranean Sea. In situations where stock assessment data is scarce, fishers’ ecological knowledge (FEK) has proven valuable for understanding the ecological status of marine resources and their historical transformations. However, FEK can be affected by memory bias, reducing its reliability, a phenomenon known as the "shifting baseline syndrome” (SBS). This study investigates the presence of SBS within Barcelona’s fishing community by comparing fishers’ perceptions of abundance changes in six commercially significant marine species in Catalonia with data from scientific stock assessments. A mixed-methods approach was employed, incorporating semi-structured interviews and the analysis of fishery-independent biological data. The findings reveal no significant discrepancies between scientific assessments and fishers’ perceptions, suggesting that SBS is not present in this fishery. However, variations in how fishers perceive these changes were identified, pointing to potential future challenges. This research provides novel evidence of fishers’ ability to offer consistent quantitative insights into the status of commercial marine species within Barcelona’s fishing sector.